STUDI TENTANG PENGARUH DANA TRANSFER, INVESTASI DAN BELANJA PEMERINTAH TERHADAP INDEKS PEMBANGUNAN MANUSIA KABUPATEN / KOTA DI JAWA TIMUR TAHUN 2009 - 2013 - Wicesa, Nayaka Artha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Result of a development is in the form of welfare thatâ€™s at the beginning difficult to be measured ultimately can be measured by the Human Development Index (HDI). HDI of Regency and City Â in East Java Province tend to increase every year and are in an intermediete position. The level of local fiscal power from the state budget namely in the form regional budget will affect a walfare of region. With a few variables have been determined, this research aims to: (1) know how to influence of transfer funds against HDI of Regency and City in East Java Province, (2) know how to influence of investment against HDI of Regency and City in East Java Province, (3) know how to influence of government expenditure againts HDI of Regency and City in East Java Province. The place and time of this research are in all districts and cities in East Java during 2009 -2013. The analytical method that will be used is the panel data regression. Results of this research using fixed effect model showed that the transfer funds, investment and government expenditure generates positive and significant impact on the human development indexKey Words : Human Development Index, Transfer Funds, Investment, Government Expenditure